2007
DOI: 10.1016/j.saa.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Raman mapping of coesite inclusions in garnet from the Kokchetav Massif (Northern Kazakhstan)

Abstract: Coesite inclusions occur in a wide range of lithologies and coesite is therefore a powerful ultrahigh-pressure (UHP) indicator. The transformation of coesite to quartz is evidenced by three optically well identifiable characteristics (e.g. palisade textures, radial crack patterns, polycrystalline quartz pseudomorphs). Under overpressure monomineralic coesite (on an optical basis), lacking the above transformation characteristics may survive. Raman micro-spectroscopy was applied on monomineralic coesite inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 36 publications
3
47
1
Order By: Relevance
“…Coesite-to-quartz transformation is accomplished with significant volume changes; very high residual pressures can be preserved in ''monomineralic'' (following the definition of Parkinson, 2000) coesite inclusions, as well as in partly transformed coesite (Parkinson & Katayama, 1999;Sobolev et al, 2000;Ye et al, 2001;Korsakov et al, 2007). The Raman shift of quartz was recently tested on natural samples in order to estimate the effect of peak metamorphic pressure on residual pressure within the quartz inclusions (Enami et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coesite-to-quartz transformation is accomplished with significant volume changes; very high residual pressures can be preserved in ''monomineralic'' (following the definition of Parkinson, 2000) coesite inclusions, as well as in partly transformed coesite (Parkinson & Katayama, 1999;Sobolev et al, 2000;Ye et al, 2001;Korsakov et al, 2007). The Raman shift of quartz was recently tested on natural samples in order to estimate the effect of peak metamorphic pressure on residual pressure within the quartz inclusions (Enami et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They have homogeneous cores whereas slight variations in their composition occur in narrow ($100 mm) external zones (Shatsky et al, 1995;Korsakov et al, 1998;Hermann et al, 2001;Korsakov et al, 2002;Korsakov & Hermann, 2006). Diamond and coesite inclusions identified in the garnet porphyroblasts point to peak metamorphic conditions of P$4-6 GPa and T$950-1000 C (Sobolev & Shatsky, 1990;Hermann et al, 2001;Korsakov et al, 2007). Higher peak metamorphic conditions of P$6-8 GPa and T ¼ 1100 C have been reported by Ota et al (2000), Massonne (2003) and Dobrzhinetskaya et al (2006).…”
Section: Sample B01-3mentioning
confidence: 92%
See 2 more Smart Citations
“…Shock-induced formation of coesite has been also observed in meteorites, where it can be found along with other shock minerals (e.g., Ohtani et al 2011). Terrestrial occurrence of coesite was reported from deeply (>100 km) subducted crustal rocks (ultrahigh-pressure metamorphic rocks) or mantle derived rocks (kimberlites), which have been exhumed under conditions that prevent retrograde transition to quartz (e.g., Smyth and Hatton 1977;Chopin 1984;Mosenfelder and Bohlen 1997;Parkinson 2000;Korsakov et al 2007;Ruiz-Cruz and Sanz de Galdeano 2012). In these rocks, coesite commonly occurs as an inclusion within clinopyroxene, olivine, garnet, or diamond.…”
Section: Introductionmentioning
confidence: 98%